Pengaruh Pemberian Konsentrasi Pupuk Organik Cair (Poc) Superbionik dan Pupuk Anorganik Terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis Hypogaea L.) Varietas Gajah - Rizki Rizkiana Gunawan; Darso Sugiono; Kasdi Pirngadi (Peneliti.net, 2021)
Peanuts (Arachis hypogaea L.) is one of the legume plants that are well known and quite important in Indonesia. The purpose of the study was to find out the concentration of Superbionic liquid organic fertilizers and inorganic fertilizers that are right for the growth and yield of the Gajah variety(Arachis hypogaea L.). The research was conducted in Sirnabaya Village of Teluk Jambe Bay District of Karawang Regency in July to October 2021. Research methods used experimental methods with Randomized Group Design (RAK) Single Factor Combinations. Treatment with several concentrations of Superbionik liquid organic fertilizer with Mutiara compound inorganic fertilizer (16:16:16) A (0 ml/1 water + 0 kg/ha Mutiara inorganic fertilizer (16:16:16) B, C, D (2 ml/1 + 125, 187.5, 250 kg/ha) E, F, G (4 ml/1 + 125, 187.5, 250 kg/ha) H, I, J (6 ml/1 water + 125, 187.5, 250 kg/ha). The results showed that there was a real influence from the combination of Superbionik liquid organic fertilizer with inorganic fertilizer on the yield of peanut plants (Arachis hypogaea L.) varieties of Gajah on the parameters of the number of leaves, the weight of dry pods per plant, and the weight of dry pods per plot. More research is needed with the same treatment with different varieties.